Impact of Revised Code NBC105 on Assessment and Design of Low Rise Reinforced Concrete Buildings in Nepal - Shrestha, Jagat K.; Paudel, Nirajan; Koirala, Bishal; Giri, Binod R.; Lamichhane, Adarsha (Journal of the Institute of Engineering, 2021)
Gorkha Earthquake in 2015 has impacted considerably in the design and construction of buildings in Nepal. Strength and Safety of life and constructions have become the prime concerns of the government and the public. Regulation is required to achieve the strength and safety in the constructions. Hence, a need for revision of building codes has been felt and Nepal Building Code, NBC105 has been revised. This paper presents the impact of the revised code on seismic load estimation for low rise reinforced concrete buildings. For the assessment of the impact linear and non- linear static and linear dynamic analysis of reinforced concrete residential buildings of two storey and four Storey has been taken subjected to Indian Standard Codes IS 1893: 2002, IS 1893:2016, Nepal Building Codes NBC 105: 1994 and NBC 105: 2020. The buildings were modeled and analyzed in SAP2000. The response of the buildings such as time period, base shear, drifts, and storey forces from the application of the four codes was compared. The comparison of the results shows that the structural response of the building under the revised NBC105:2020 is 60% to 65% higher compared to the previous code NBC105:1994.